1991
DOI: 10.1177/0887302x9101000106
|View full text |Cite
|
Sign up to set email alerts
|

Social Values and Fashion Leadership

Abstract: Because fashion leadership among women is of great interest to clothing researchers and retailers alike, much effort has been devoted to studying the demographic characteristics of women who can be identified as fashion leaders. Although demographic data provide valuable information, demographics alone give little insight into the forces that motivate women to become fashion leaders. Beyond demographic factors, personal and social values have been argued to have an important influence on the strength and direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
78
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(84 citation statements)
references
References 20 publications
4
78
0
2
Order By: Relevance
“…Kleding wat te veel soos dié van die groep lyk, word daarenteen verwerp. Item 1 kan ook beskou word as 'n behoefte aan vertoon, selfs spel en genot (Goldsmith et al, 1991) en uiteindelik as 'n behoefte om te presteer deur besonderse skoene uit te soek.…”
Section: Individualistiese Kledingbehoeftesunclassified
“…Kleding wat te veel soos dié van die groep lyk, word daarenteen verwerp. Item 1 kan ook beskou word as 'n behoefte aan vertoon, selfs spel en genot (Goldsmith et al, 1991) en uiteindelik as 'n behoefte om te presteer deur besonderse skoene uit te soek.…”
Section: Individualistiese Kledingbehoeftesunclassified
“…Also, fashion leaders tend to be more confident in their information and their own taste (Kaiser, 1990). From the behavioral perspective, fashion leaders are more likely to acquire information on fashion through fashion magazines and attend fashion shows (Goldsmith Heitmeyer, & Freiden, 1991;Mason & Belleger, 1973-74), to spend more time and money for fashion items (Goldsmith et al, 1991), and to adopt new fashion items faster than others (Kaiser, 1990). Such characteristics are also observed in digital environments, as fashion leadership has been show to positively influences WOM communication through SNS (Park, Chung, & Jeon, 2012).…”
Section: ) Fashion Leadershipmentioning
confidence: 99%
“…High fashion leaders are the first to buy and wear new fashions, persuading others to follow [41]. Research shows that fashion leadership purchasers differ in many consumer behaviors, including their evaluation and purchasing of products [7,[17][18][19][20][21]42]. …”
Section: Fashion Leadershipmentioning
confidence: 99%
“…Research has investigated the influence of clothing attributes on consumers' purchase intentions and found that consumers are significantly influenced by different attributes when determining overall acceptance of fashion products [12][13][14][15][16]. In the case of fashion items, an additional consideration is fashion leadership which influences product evaluation and purchasing of products [7,[17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation